Menelaah Permasalahan Keamanan Non-Tradisional (Human Trafficking) di Thailand: Analisis Konstruktivisme - Nur Ainun Musdalifah (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
Human Trafficking is a non-traditional security issue that is of particular concern for the Southeast Asian region. Thailand is the country that is most highlighted for this case, especially in sexual exploitation in the form of prostitution. Prostitution in Thailand is even included in the category of tourism for foreign tourists. This prostitution tourism contributes 60% of the country's income for the tourism sector, exceeding half of tourism income. Prostitution tourism is certainly very closely related to human trafficking, as can be seen in commercial sex workers (CSWs) who are mostly minors and women. The deep-rooted culture is a trigger for the rise of CSWs who mostly come from rural communities. The culture that comes from Buddhism as the largest teaching in Thailand is